2021
DOI: 10.1007/s10140-020-01884-0
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and venous thromboembolic complications of COVID-19 detected by CT angiogram and venous duplex ultrasound

Abstract: Objective To investigate the incidence of thromboembolic events, specifically pulmonary embolism (PE), deep vein thrombosis (DVT), and cerebrovascular accidents (CVA), in patients who tested positive for COVID-19 through RT-PCR in a regional healthcare system in Connecticut. Materials and methods All CT angiogram (CTA) and venous duplex extremity ultrasound (US) examinations performed on 192 consecutively documented cases of COVID-19 were retrospectively reviewed at a multi-centered healthcare system. Clinical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In total, 32 hospital cohort and database studies with follow-up ranging from 6.8 days (median duration of hospitalization) to 198 days (maximum follow-up period for patients in hospital at the end of the enrollment period) were included in the literature review (Table 1). Of these, 26 studies described analyses of hospital (or multi-hospital) records, and included outpatients (three studies), [8][9][10] patients treated in emergency departments (EDs; two studies) 11,12 and patients treated in hospital (22 studies) 8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] ; six studies described cohorts treated in ICU. 10,15,17,24,26,32 A single study followed patients discharged after hospitalization for COVID-19.…”
Section: Summary Of Hospital Cohort and Database Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 32 hospital cohort and database studies with follow-up ranging from 6.8 days (median duration of hospitalization) to 198 days (maximum follow-up period for patients in hospital at the end of the enrollment period) were included in the literature review (Table 1). Of these, 26 studies described analyses of hospital (or multi-hospital) records, and included outpatients (three studies), [8][9][10] patients treated in emergency departments (EDs; two studies) 11,12 and patients treated in hospital (22 studies) 8,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] ; six studies described cohorts treated in ICU. 10,15,17,24,26,32 A single study followed patients discharged after hospitalization for COVID-19.…”
Section: Summary Of Hospital Cohort and Database Studiesmentioning
confidence: 99%
“…Across the included studies, PE was reported by a median of 0.4% of outpatients, [7][8][9][10][11][12][36][37][38] 2.3% of patients admitted to hospital, 8,10,[13][14][15][16][18][19][20][21][22][23][25][26][27][28][29][30][31][32][33][34][35]37 and 7.3% of patients treated in ICU 15,17,24,26,32 (Figure 2a). In analyses of patients who all underwent CTPA, PE was reported by a median of 34.2% of outpatients treated in ED, 11,12 8.3% of previously discharged outpatients (in a single study), 7 18.5% of hospitalized patients, 9,13,18,21,27,29,31 22.1% of hospitalized non-ICU ...…”
Section: Overall Incidence Of Pementioning
confidence: 99%
“…[14]. In our review, 12 studies found an incidence of PE ranging from 2.8 to 57%, with patients admitted to the ICU experiencing PE at significantly higher rates [3,5,[15][16][17][18][19][20][21][22][23][24]. Though isolated COVID-19 infection represented the most common indication for CTPA imaging request, clinically apparent dyspnea, hypoxia or increasing oxygen requirement, chest pain, hemoptysis, and tachycardia, as well as elevated D-dimer, were the most common indications for additional imaging [22].…”
Section: Pulmonary Embolismmentioning
confidence: 84%
“…Most cases of COVID-19–related DVT have been described in the lower extremities, either in the calf musculature and popliteal vein or the femoral vein with central propagation. Classic findings of acute venous thrombosis are best diagnosed at gray-scale and color and spectral Doppler US ( 38 ).…”
Section: Covid-19 In Msk Systemmentioning
confidence: 99%
“…CT angiography is the study of choice to help diagnose arterial thrombosis, with classic imaging findings well described in the literature ( 38 ). Simultaneous imaging of the contralateral extremity may help to detect subtle abnormalities ( Fig 11 ).…”
Section: Covid-19 In Msk Systemmentioning
confidence: 99%